Establishing the Brief Assessment of Cognition - Short form. (October 2017) - Lam, Max; Wang, Mingyuan; Huang, Wanping; Eng, Goi Khia; Rapisarda, Attilio; Kraus, Michael; Kang, Sim; Keefe, R.S.E.; Lee, Jimmy
Abstract: The study aims to identify and validate a parsimonious subset of tests in the commonly used Brief Assessment of Cognition in Schizophrenia (BACS) that allows the evaluation of global cognitive ability. Several permutations of subtests from the BACS were examined to identify the best subset of tests to compose the short form measure. The Brief Assessment of Cognition-Short Form (BAC-SF) was evaluated for convergent validity in healthy and psychiatric samples (N = 3718). Verbal Memory, Digit Sequencing, and Symbol Coding subtests were found to best summarize the variance of composite scores in both Asian and US Norming samples (r = 0.91) indicating that BAC-SF is an appropriate approximation of cognitive deficits. Test re-test reliability of the BAC-SF was adequate (Intraclass Correlation Coefficient (ICC) = 0.73) and showed sufficient separation between healthy controls and schizophrenia (Average Predictive Accuracy = 79.9%; replication = 76.5%). Findings indicate that the BAC-SF an could be used as a cognitive screener for large-scale clinical and epidemiological studies. The short form does not replace the need for comprehensive neuropsychological batteries purposed for detailed neuropsychological and clinical investigation of cognitive function. Further replication of the construct might be necessary in other clinical populations.